Bảng so sánh, giải trình các quy định tại Dự thảo Nghị quyết về xử lý nợ xấu của các tổ chức tín dụng (2017)
Bảng so sánh, giải trình các quy định tại Dự thảo Nghị quyết về xử lý nợ xấu của các tổ chức tín dụng được so sánh, giải trình các quy định tại Dự thảo Nghị quyết.